« Your Body is a Battleground » De quelques objets de l'histoire de l'art - Mader, Rachel; Schweizer, Nicole (Nouvelles Questions Féministes, 2005)
Notre article s'articule autour des points suivants: comment la critique féministe de histoire de l'art a-t-elle déplacé le ou les «objets» autour desquels s'articulait traditionnellement la discipline? Quels nouveaux «objets» ont dès lors été constitués? Et comment, à l'épreuve de ceux-ci, les histoires de l'art féministes doivent-elles, elles aussi, constamment se repositionner? L'exemple paradigmatique du corps dans la performance des années 70 nous permet d'interroger dans un deuxième temps la façon dont les artistes elles-mêmes ont déplacé la définition de l'objet, et par conséquent aussi celle du sujet - de l'œuvre comme de la perception.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; artistes féministes; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; performance; premier cycle; périodes historiques; représentation des femme*; ressource en ligne; sex2283; sexisme; systèmes d'oppressions; thématiques

Women making art: history, subjectivity, aesthetics - Meskimmon, Marsha.. (Routledge, 2003)
Women have been making art for centuries, yet their work has been seen as secondary or has gone unrecognized altogether. "Women making art" asks why this is so, and what it would take for us to realize the extent of women's extraordinary contribution to the arts. Marsha Meskimmon mobilizes contemporary feminist thinking to reconsider how and why women have made art. She examines work by a wide range of women artists fomr different cultures and historical periods, including Rebecca Horn, Rachel Whiteread, Shirin Neshat and Maya Lin, emphasizing the diversity of women's arts and the importance of differences between women.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Women in Dada: essays on sex, gender, and identity - Sawelson-Gorse, Naomi (The MIT Press, 2001)
Finally, a look at the role of women in the shaping of the high-spirited—but hardly feminist—Dada monement. For all of its iconoclasm, the Dada spirit was not without repression, and the Dada movement was not without misogynist tendencies. Indeed, the word Dada evokes the idea of the male—both as father and as domineering authority. Thus female colleagues were to be seen not heard, nurturers not usurpers, pleasant not disruptive.This book is the first to make the case that women's changing role in European and American society was critical to Dada. Debates about birth control and suffrage, a declining male population and expanding female workforce, the emergence of the New Woman, and Freudianism were among the forces that contributed to the Dadaist enterprise. Among the female dadaists discussed are the German émigré Baroness Elsa von Freytag-Loringhoven; Berlin dadaist Hannah Höch; French dadaists Juliette Roche and Suzanne Duchamp; Zurich dadaists Sophie Taeuber and Emmy Hennings; expatriate poet and artist Mina Loy; the "Queen of Greenwich Village," Clara Tice; Margaret Anderson and Jane Heap, the lesbian couple who ran The Little Review; and Beatrice Wood, who died in 1998 at the age of 105. The book also addresses issues of colonialist racism, cross-dressing and dandyism, and the gendering of the machine. The bibliography was compiled by the International Dada Archive (Timothy Shipe and Rudolf E. Kuenzli). Contributors Eleanor S. Apter, Barbara J. Bloemink, Willard Bohn, Carolyn Burke, William A. Camfield, Whitney Chadwick, Dorothea Dietrich, Susan Fillin-Yeh, Paul B. Franklin, Renée Riese Hubert, Marisa Januzzi, Amelia Jones, Marie T. Keller, Rudolf E. Kuenzli, Maud Lavin, Margaret A. Morgan, Dickran Tashjian, Elizabeth Hutton Turner, Barbara Zabel
Keywords: 1900-1999; 1910-1919; allemagne; amériques; approches et analyses; arts; cours; discipline; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; régions géographiques; sexisme; suisse; systèmes d'oppressions; thématiques; états-unis